2021
DOI: 10.1038/s41598-021-88563-3
|View full text |Cite
|
Sign up to set email alerts
|

Rbm24 displays dynamic functions required for myogenic differentiation during muscle regeneration

Abstract: Skeletal muscle has a remarkable capacity of regeneration after injury, but the regulatory network underlying this repair process remains elusive. RNA-binding proteins play key roles in the post-transcriptional regulation of gene expression and the maintenance of tissue homeostasis and plasticity. Rbm24 regulates myogenic differentiation during early development, but its implication in adult muscle is poorly understood. Here we show that it exerts multiple functions in muscle regeneration. Consistent with its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Members of the RNA-binding motif (RBM) family are upregulated in myoblasts, myotubes and adult muscle and play roles in alternative splicing via splice site selection. Interestingly, several studies have shown that, for example, RBM5 regulates the cell cycle and apoptosis while RBM24 is important for striated muscle differentiation, thus integrating well in our analysis so far [63,64]. Survival motor neurons 1 and 2 (SMN1/2) are downregulated in both proliferating and differentiated muscle cells twofold.…”
Section: Splicing As the Basis Of Pathway Alterationssupporting
confidence: 77%
“…Members of the RNA-binding motif (RBM) family are upregulated in myoblasts, myotubes and adult muscle and play roles in alternative splicing via splice site selection. Interestingly, several studies have shown that, for example, RBM5 regulates the cell cycle and apoptosis while RBM24 is important for striated muscle differentiation, thus integrating well in our analysis so far [63,64]. Survival motor neurons 1 and 2 (SMN1/2) are downregulated in both proliferating and differentiated muscle cells twofold.…”
Section: Splicing As the Basis Of Pathway Alterationssupporting
confidence: 77%
“…A related aspect is the lack of systematic examination of RBM24 subcellular localization in cancer cells. It has been shown that RBM24 displays dynamic cytoplasm to nucleus translocation during cellular differentiation, which is correlated with a shift from regulating mRNA stability to coordinating tissue-specific pre-mRNA splicing [ 27 ]. Importantly, data from the Human Protein Atlas indicate that RBM24 displays heterogeneous subcellular distribution in specific cancer tissues with a population of cells showing nuclear localization.…”
Section: Discussionmentioning
confidence: 99%
“…RBM24 exhibits strongly restricted expression in skeletal muscle and in the heart during vertebrate development [ 18 ]. It also shows cytoplasm-to-nucleus translocation during myogenesis and dynamic post-transcriptional functions during muscle regeneration mediated by muscle stem cells [ 27 ]. In several animal models, loss of RBM24 activity has been shown to inhibit myogenic differentiation [ 18 , 61 ] and impair cardiogenesis [ 22 , 24 , 62 , 63 , 64 ] and vasculogenesis [ 62 ].…”
Section: Rbm24 In Cancer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works indicate that a majority of muscle-specific splicing defects caused by loss of Rbm24 in mice are also present in zebrafish rbm24a mutants, suggesting conserved mechanisms underlying RBM24 function in muscle development (Shao et al, 2020). However, the stability of several mRNAs encoding proteins critically involved in muscular function is also reduced in rbm24a mutants (Cheng et al, 2020), such as Smpx (small muscle protein X-linked) that functions to promote myocyte fusion by increasing the activity of NFAT (nuclear factor of activated T cells) and MEF2 transcription factors via IGF1 (insulin-like growth factor 1) signaling (Palmer et al, 2001). Smpx plays important roles in muscle fiber organization and distal myopathy (Ghilardi et al, 2021;Johari et al, 2021).…”
Section: Rna Binding Motif Protein 24 Is Required For Embryonic Myogenesis and Adult Skeletal Muscle Regenerationmentioning
confidence: 99%